Comparative analysis of literary translations of poet I. Yusupov's "Shogirme" poem in Uzbek and English (Ta'limning zamonaviy transformatsiyasi, 2024)
This article aims to discuss the translation of contemporary Karakalpak poets’ works into Uzbek and English and how national clothing names are reflected in them.